Phytochemical characterization, antimicrobial activity, and antioxidant potential of Equisetum hyemale L. (Equisetaceae) extracts - Queiroz, Geisiany M. de[UNESP]; Politi, Flávio A. S. [UNESP]; Rodrigues, Edvânio R. [UNESP]; Souza-Moreira, Tatiana M. [UNESP]; Moreira, Raquel R. D. [UNESP]; Cardoso, Cássia R. P. [UNESP]; Santos, Lourdes C. [UNESP]; Pietro, Rosemeire C. L. R. [UNESP] (Journal of Medicinal Food, 2015)
Equisetum hyemale species is considered a medicinal plant used in the form of infusions to combat infectious or inflammation diseases and also diuretic effects, presenting several compounds related to these actions. In previous studies different species of Equisetum showed several phenolic compounds. The objective of this study was, for the first time, based on phytochemistry analysis to evaluate the antioxidant and antimicrobial activity. The 70% ethanolic and methanolic extracts of E. hyemale were characterized by spectrophotometric and high-performance liquid chromatography with pulsed amperometric detector analyses, as well as its antioxidant potential based on the scavenger activity of 2,2-diphenyl-1-picrylhydrazyl (DPPH). In addition was verified the antimicrobial activity by broth microdilution technique against bacteria and fungi. The extracts showed phytochemical similarity, which demonstrated the presence of phenolic compounds, the scavenging activity for free radicals was about 30% and was observed better antifungal activity against dermatophyte fungi, with minimum inhibitory concentration and minimum fungicidal concentration of 0.62 mg/mL to Trichophyton rubrum and Microsporum canis. The extracts exhibits great potential to therapeutic applications or product development, since both possess antifungal activity and antioxidant action associated with little difference in their phytochemical composition.
Keywords: Equisetum hyemale; Mic; Antimicrobial activity; Antioxidant effect; Medicinal plant analysis; Phytochemistry